Soames on vagueness - Williamson, T (Wiley-Blackwell, 2002)
Scott Soames has a justly high reputation for the precision and rigour of his work in the philosophy of language. It is therefore with considerable interest that one turns to the chapter of "Understanding Truth" on vagueness and the sorites paradox to see what he has to say.